Tempered Tempos: The Politics of Waiting for Public Services in Contemporary Cape Town - Pakleppa, Yoni (African Studies, 2020)
This dissertation recognises that waiting for public services in South Africa is becoming an increasingly important point of contestation between the state and its citizens. Rather than exploring the spectacular expressions of this tension seen in ongoing service delivery protests, it foregrounds the everyday experiences of waiting for public services at three key sites in Cape Town: the dispersed everyday waiting for public transport at train stations; the queues at the Department of Home Affairs regional office for South African Identity Document applications; and the waiting room of the Chapel Street Community Health Clinic. In relation to each of these sites, it engages the ethnographic method to investigate who waits for what and for how long, what this waiting entails, and the meanings that those who wait draw from these lengthy and repeated experiences. The dissertation consists of three chapters which put into conversation the connections between postcolonial infrastructural crises, socially fractured temporal experiences, and the everyday culture of interaction with the state. By tracing the history of how infrastructures and systems of delivery were designed to support first the project of colonial modernity, and later the project of apartheid, it explains why the experience of waiting is so prominent in accessing public services in this particular context. It then moves away from the contextual to focus on how these broad frameworks manifest in individuated everyday experiences of waiting. It finds that despite the fact that the modes of waiting vary significantly between sites, in all three, waiting is socially fractured and decidedly uneven, in both obvious and unseen ways. Lastly, it considers the diverse effects of waiting to conclude that although waiting can impel people to patiently endure, there are also moments when waiting is challenged, resisted, and redeployed in the popular domain to take on new and empowering meanings.